Seasonal and Spatial Environmental Influence on Opisthorchis viverrini Intermediate Hosts, Abundance, and Distribution: Insights on Transmission Dynamics and Sustainable Control. - Christina Sunyoung Kim; Pierre Echaubard; Apiporn Suwannatrai; Sasithorn Kaewkes; Bruce A Wilcox; Banchob Sripa (Public Library of Science (PLoS), 2016)
BACKGROUND:Opisthorchis viverrini (Ov) is a complex-life-cycle trematode affecting 10 million people in SEA (Southeast Asia). Human infection occurs when infected cyprinid fish are consumed raw or undercooked. Ov requires three hosts and presents two free-living parasitic stages. As a consequence Ov transmission and infection in intermediate and human hosts are strongly mediated by environmental factors and understanding how environmental variability influences intermediate host abundance is critical. The objectives of this study were 1) to document water parameters, intermediate hosts abundance and infection spatio-temporal variation, 2) to assess their causal relationships and identify windows of transmission risk. METHODOLOGY/PRINCIPAL FINDINGS:Fish and snails were collected monthly for one year at 12 sites in Lawa Lake, an Ov-endemic region of Khon Kaen Province in Northeast Thailand. Physicochemical water parameters [pH, temperature (Tp), dissolved oxygen (DO), Salinity, electrical conductivity (EC), total dissolved solid (TDS), nitrite nitrogen (NO2-N), lead (Pb), total coliform bacteria (TCB) and fecal coliform bacteria (FCB)] were measured. Multivariate analyses, linear models and kriging were used to characterize water parameter variation and its influence on host abundance and infection prevalence. We found that sampling sites could be grouped in three clusters and discriminated along a nitrogen-salinity gradient where higher levels in the lake's southern region predicted higher Bithynia relative abundance (P<0.05) and lower snail and fish species diversity (P<0.05). Highest Bithynia abundance occurred during rainy season (P<0.001), independently of site influence. Cyprinids were the most abundant fish family and higher cyprinid relative abundance was found in areas with higher Bithynia relative abundance (P<0.05). Ov infection in snails was anecdotal while Ov infection in fish was higher in the southern region (P<0.001) at sites showing high FCB. CONCLUSIONS/SIGNIFICANCE:Our results indicate that water contamination and waterways configuration can influence freshwater communities' assemblages possibly creating ideal conditions for sustained transmission. Sustainable control may require a better appreciation of the system's ecology with wise governance and development planning particularly in the current context of SEA agricultural intensification and landscape modification.